Pengaruh Brand Ambassador dan Tagline Terhadap Respon Khalayak Pada Brand MS Glow For Men - Yosephine Clarisa Tasya Kusuma Putri; Rah Utami Nugrahani (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
MS Glow For Men is a men's skincare brand that uses brand ambassadors Babecabita and Marshel Widianto, as well as the tagline #SemuaJugabisa, to communicate. s. The purpose of this study was to examine and analyze the presence and extent of the influence of MS Glow For Men Brand Ambassador and Tagline on Audience Response, either partially or simultaneously. The effect of brand ambassadors and taglines on audience responses in this study will be measured through the theory of the hierarchy of effects model, which consists of 3 stages: cognitive, affective, and behavior. A quantitative research method was used, which included multiple linear regression analysis techniques and partial correlation. Non-probability sampling was used in a purposive sampling approach, tested on 100 respondents. According to the findings of this study, there is a partial influence of the brand ambassador and tagline, both of which have t count > t table and a significant value of 0.05. The brand ambassador has a strong influence of 57.3049 percent on the audience's response, while the tagline strongly influences 38.1924 percent. It was discovered that brand ambassadors and taglines significantly and positively influenced audience responses. Fcount 84.139 > Ftable 3.09 and a significance value of 0.000 0.5 support this. According to the coefficient of determination results, brand ambassadors and taglines had a 63.4 percent effect on audience responses, while factors outside the study influenced 36.6 percent.